SEHAT SEJAK DINI, BEBAS DIABETES, HIDUP SEHAT DI APOTEK MURAH KANDANGAN: Health From an Early Age, Free from Diabetes, Healthy Living at Apotek Murah Kandangan - Thaibah, Hayatun; Mardiati, Nurul (Program Studi Sastra Indonesia Universitas Mulawarman, 2025)
Abstract: This health promotion activity aimed to educate and inform the public about diabetes at Apotek Murah Kandangan. Diabetes mellitus is a chronic disease characterized by elevated blood sugar levels. Early detection and prevention are crucial given the increasing prevalence and potential complications of diabetes, especially in children and the elderly. The promotion was conducted through an educational video posted on the Instagram account of Apotek Murah Kandangan, with the theme